Determinant Factors Influencing Malaria Incidence in an Endemic Area of Sumbawa, Indonesia - Hasifah, Herni; Rinenggantyas, Nikodimus Margo (Biomedical Journal of Indonesia, 2025)
Introduction. Indonesia still records the incidence of malaria every year, as several malaria cases still occur in the country. Contributing factors and community aspects have a noteworthy effect on any malaria elimination activities. Methods. This study is a correlational study with a cross-sectional time approach. The population in this study were 59 respondents in Ropang sub-district, Sumbawa. The sampling technique used was simple random sampling. Bivariate analysis of statistical tests used was logistic regression. Results. There are two variables that have a significant effect on the incidence of malaria, namely knowledge and preventive behavior. The knowledge variable had a significance value of 0.019 (p < 0.05), and an odds ratio value of 0.235. The preventive behavior variable also showed a significant influence on malaria incidence with a significance value of 0.008 (p < 0.05). Meanwhile, the perception variable did not show a significant effect on the incidence of malaria, with a significance value of 0.359 (p> 0.05). Conclusion. The results of this study showed that knowledge and preventive behavior had a significant effect on the incidence of malaria in respondents, while perception did not show a statistically significant relationship. These findings provide a new contribution to the understanding of the determinants of malaria prevention behavior in the study area.